2023
DOI: 10.15252/embj.2022112534
|View full text |Cite
|
Sign up to set email alerts
|

Selective autophagy regulates chloroplast protein import and promotes plant stress tolerance

Chen Wan,
Hui Zhang,
Hongying Cheng
et al.

Abstract: Chloroplasts are plant organelles responsible for photosynthesis and environmental sensing. Most chloroplast proteins are imported from the cytosol through the translocon at the outer envelope membrane of chloroplasts (TOC). Previous work has shown that TOC components are regulated by the ubiquitin‐proteasome system (UPS) to control the chloroplast proteome, which is crucial for the organelle's function and plant development. Here, we demonstrate that the TOC apparatus is also subject to K63‐linked polyubiquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…NBR1 (Next to BRCA1 gene 1), are responsible for autophagic degradation of ubiquitinated NBR1 targets cargo and physically interacts with the ATG8 protein to promote cargo envelopment into autophagosomes [32]. NBR1 protein content was slightly lower in overexpressing AtATG8a and AtATG8g seedlings [31], suggesting that NBR1 degradation was stimulated in the ATG8 overexpression.…”
Section: Resultsmentioning
confidence: 99%
“…NBR1 (Next to BRCA1 gene 1), are responsible for autophagic degradation of ubiquitinated NBR1 targets cargo and physically interacts with the ATG8 protein to promote cargo envelopment into autophagosomes [32]. NBR1 protein content was slightly lower in overexpressing AtATG8a and AtATG8g seedlings [31], suggesting that NBR1 degradation was stimulated in the ATG8 overexpression.…”
Section: Resultsmentioning
confidence: 99%
“…Chloroplasts are the most important sites for photosynthesis. Two new studies have shown that autophagy is extensively involved in chloroplast degradation under abiotic stress, which may be one of the main reasons for the decline in plant photosynthetic capacity 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…For years, autophagy has been recognized for its role in bulk and non-selective degradation of cytoplasmic constituents and organelles, particularly under conditions such as senescence or starvation. However, more studies have shed light on a new aspect of autophagy functionality: selective autophagy ( Derrien et al , 2012 ; Floyd et al , 2015 ; Thirumalaikumar et al , 2021 ; Tong et al , 2023 ; Wan et al , 2023 ). These studies have demonstrated that autophagy can operate selectively, targeting specific cellular components or macromolecules for degradation ( Fig.…”
Section: Autophagy-mediated Degradation: Mechanisms and Significancementioning
confidence: 99%
“…Selective autophagy efficiently disposes of damaged or unneeded macromolecules (e.g. proteins and RNAs) or even organelles, as well as protein aggregates ( Derrien et al , 2012 ; Zhou et al , 2013 ; Floyd et al , 2015 ; Michaeli et al , 2016 , 2019 ; Tong et al , 2023 ; Wan et al , 2023 ). Autophagy is active in cells under normal growth conditions, operating at a basal level to maintain cellular homeostasis.…”
Section: Autophagy-mediated Degradation: Mechanisms and Significancementioning
confidence: 99%
See 1 more Smart Citation